A Framework for Operationalizing Climate-Just Ocean Commitments Under the Paris Agreement - Reiter, Sarah M.; Cheng, Laura M.; Pouponneau, Angelique; Taylor, Sophie; Wedding, Lisa M. (Frontiers in Climate, 2021)
Building on the considerable momentum from the commencement of the Decade of Ocean Science, the Ocean-climate nexus will be center stage at COP26. Many countries are including blue carbon Ocean commitments in their second round of nationally determined contributions (NDCs), and there is a need to harmonize the science, law, and economics of Ocean-based climate mitigation and adaptation strategies to enable implementation of Ocean commitments under the Paris Agreement. In addition, consistent with the Paris Agreement preamble’s focus on human rights, the rights and empowerment of vulnerable and marginalized communities, and intergenerational equity, the design and implementation of Ocean commitments in NDCs should be centered on considerations of climate justice (“climate-just Ocean commitments”). The challenges and opportunities inherent in implementing climate-just Ocean commitments require a comprehensive review of the latest innovations in blue carbon scientific research, the enabling conditions necessary for uptake of this science into policies and decision making, and the financial structures needed to equitably finance Ocean nature-based solutions. Responding to this need, we propose that a framework is needed to support the inclusion of blue carbon sequestration potential in ambitious national and subnational action. The proposed framework should center on the intersectionality of climate justice with the three key layers essential to implementation of Ocean commitments – science, law, and economics- where traditional and local ecological knowledge is valued on par with western science, law and policy centers on vulnerable communities, and financial mechanisms respect national sovereignty, value local cultures, and support sustainable economic development.